Pengaruh CR dan ROA Terhadap Harga Saham Perusahaan Dagang Yang Terdaftar di BEI Periode 2019 - 2023 - Desi Ratnasari; Fenny Yulita; Okta Nia Ramadhani (Journal of Research and Publication Innovation, 2025)
This study looks at how the Current Ratio (CR) and Return on Assets (ROA) affect the share prices of 15 trading companies that are listed on the Indonesia Stock Exchange (BEI) between 2019 and 2023. Prices, corporate shares, and financial reports that may be read on the official IDX website provide the secondary data that is used. An analytical method used to examine the link and impact of independent variables (ROA and CR) on the dependent variable (share price) is multiple linear regression.